INNOVATIVE ASSESSMENT SYSTEMS IN ART EDUCATION AND THEIR EFFECTIVENESS - Abdullayeva Fotima Safar qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines innovative assessment systems in art education and evaluates their effectiveness in enhancing student learning and creativity. It explores formative and summative assessment methods, digital portfolios, peer review, and project-based evaluations as tools for monitoring students’ progress and fostering artistic competencies. The study emphasizes the importance of integrating innovative assessment strategies to improve motivation, engagement, and critical thinking in contemporary art classrooms.